The Local Genius Typography as a Source of Idea for Latin-based Typeface Design in Visual Communication Today - Naomi Haswanto (ITB Journal Publisher, LPPM ITB, 2013)
During its long history, slowly but sure, Indonesia had accepted the influence of the written language from various nation and civilization. Approximately in the 15th century AD, European brought their language system, Latin, to Indonesia, which had been developed until present time. The usage of Latin alphabet for daily communication in Indonesia has created a disadvantage for the local/ethnic language, especially since the Latin provided an easier writing and speaking system. Latin uses alphabet system in which one sound represents one letter: A, B, C, etc. In contrast, the ethnic language uses syllable system in which one sound could consist of more than one letter (a, ba, ta, ka, nga, kha, etc). The growing of the nation of Indonesia with its various ethnic groups created the need for unification language, a language with a universal system. Furthermore, the alphabet system is easier to be used for various written and spoken language in the world. The richness of ethnic alphabet from Indonesia could become infinite ideas in developing computer typefaces. A typographer could design Latin alphabet with the characteristic of ethnic alphabets by capturing the traditional elements from the letters. These findings could enrich the field of visual communication nowadays.